Into the blue: The role of the ocean in climate policy. Europe needs to clarify the balance between protection and use - Miranda Böttcher; Oliver Geden; Felix Schenuit (Stiftung Wissenschaft und Politik (SWP), 2023)
Since net zero targets have become a keystone of climate policy, more thought is being given to actively removing carbon dioxide from the atmosphere while continuing to drastically reduce emissions. The ocean plays a major role in regulating the global climate by absorbing a large proportion of anthropogenic carbon dioxide emissions. As the challenges of land-based carbon dioxide removal (CDR) approaches are increasingly recognised, the ocean may become the new 'blue' frontier for carbon removal and storage strategies in the EU and beyond. However, the ocean is not an 'open frontier'; rather, it is a domain of overlapping and sometimes conflicting rights and obligations. There is a tension between the sovereign right of states to use ocean resources within their exclusive economic zones and the international obligation to protect the ocean as a global commons. The EU and its Member States need to clarify the balance between the protection and use paradigms in ocean governance when considering treating the ocean as an enhanced carbon sink or storage site. Facilitating linkages between the ongoing review of the Marine Strategy Framework Directive and the establishment of the Carbon Removal Certification Framework could help pave the way for debate about trade-offs and synergies in marine ecosystem protection and use.
Keywords: 320; climate policy; net zero targets; removing carbon dioxide from the atmosphere; reduce emissions; carbon dioxide removal (CDR); ocean governance; Marine Strategy Framework Directive; UN Ocean Conference; Intergovernmental Panel on Climate Change (IPCC); United Nations Framework Convention on Climate Change (UNFCCC)